O trabalho profissional de assistentes sociais junto aos movimentos sociais de moradia que enfrentam remoções forçadas - Almeida, Lucas Lopes de (2023)
This master’s dissertation seeks to deepen the debate about the professional work of Social Workers with social housing movements that face forced evictions, understanding the elements of the socio-historical formation of a country located in the periphery of capitalism and permeated by inequality in access to land. We observe the systematic production of expulsions of the working population from their homes, due to the interests of the real estate market. This reality is exponentiated in a conjuncture marked by the financialization of capital, the offensive of the neoliberal ideology in social policies, and the worsening of the conditions of existence in society. The methodology is composed by the bibliographic research on the disputes between social classes in the urban space, in its relations of expropriation by the hegemonically dominant class, and the resistance of workers to these violent onslaughts. The empirical research was developed through interviews with two popular leaders and two social workers who have a history of working with housing movements in the central region of São Paulo. The instruments were made up of scripts with open questions that allowed for a significant collection of information and qualitative analysis about the relations between the aspects present in the narratives and that dialog with the study. The results of the research contribute to the apprehension of the forms of resistance built by housing movements against urban violations, the multiple impacts of forced evictions for families, and the materialization of the professional practice of social work with collective subjects in a relationship guided by the commitment to the interests of the working class, expressing elements that constitute the professional ethical-political project